Diagnostic pitfall of localized lentigo accompanied by post-inflammatory pigmentation on the palm with a several-month history - Keisuke Imafuku; Hiroo Hata; Shinya Kitamura; Toshifumi Nomura; Hiroshi Shimizu (Our Dermatology Online, 2015)
When dermatologists see acquired and wellcircumscribed pigmented macules on the palm, dorsal hand or forearm of the elderly, they tend to consider blue nevus, hematoma, nevus cell nevus and malignant melanoma as differential diagnoses [1].